Best practices for the design, laboratory analysis, and reporting of trials involving fatty acids. Issue 2 (21st June 2018) - Brenna, J Thomas; Plourde, Mélanie; Stark, Ken D; Jones, Peter J; Lin, Yu-Hong
ABSTRACT: Fatty acids are among the most studied nutrients in human metabolism and health. Endogenous fatty acid status influences health and disease via multiple mechanisms at all stages of the life cycle. Despite widespread interest, attempts to summarize the results of multiple studies addressing similar fatty acid–related outcomes via meta-analyses and systematic reviews have been disappointing, largely because of heterogeneity in study design, sampling, and laboratory and data analyses. Our purpose is to recommend best practices for fatty acid clinical nutrition and medical studies. Key issues in study design include judicious choice of sampled endogenous pools for fatty acid analysis, considering relevant physiologic state, duration of intervention and/or observation, consideration of specific fatty acid dynamics to link intake and endogenous concentrations, and interpretation of results with respect to known fatty acid ranges. Key laboratory considerations include proper sample storage, use of sample preparation methods known to be fit-for-purpose via published validation studies, detailed reporting or methods to establish proper fatty acid identification, and quantitative analysis, including calibration of differential response, quality control procedures, and reporting of data on a minimal set of fatty acids to enable comprehensive interpretation. We present a checklist of recommendations for fatty acid best practices to facilitate design, review, and evaluation of studies with the intention of improving study reproducibility.